1987
DOI: 10.1007/bf01871187
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostaglandins and leukotrienes in volume regulation by Ehrlich ascites tumor cells

Abstract: PGE2 and LTC4 syntheses in Ehrlich ascites cells were measured by radioimmunoassay. Hypotonic swelling results in stimulation of the leukotriene synthesis and a concomitant reduction in the prostaglandin synthesis. If the cells have access to sufficient arachidonic acid there is a parallel increase in the synthesis of both leukotrienes and prostaglandins following hypotonic exposure. PGE2 significantly inhibits regulatory volume decrease (RVD) following hypotonic swelling in Na-containing medium but not in Na-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 28 publications
5
82
2
Order By: Relevance
“…Our data and other reports as well (39,40) demonstrate that tumor cells produce PGE 2 , which is known to be cytocidal for immunocytes (41,42). Kolenko et al (21) also reported that PGE 2 can down-regulate the expression of ␥c expression and Jak-3 activity in T cells.…”
Section: Discussionsupporting
confidence: 84%
“…Our data and other reports as well (39,40) demonstrate that tumor cells produce PGE 2 , which is known to be cytocidal for immunocytes (41,42). Kolenko et al (21) also reported that PGE 2 can down-regulate the expression of ␥c expression and Jak-3 activity in T cells.…”
Section: Discussionsupporting
confidence: 84%
“…12 The series of events between a hypotonic challenge and COX-2 activity in JG cells is likely to include cell swelling and PLA 2 activation as observed in several cell types. 9 Hypotonicity-induced stimulation of COX-2 activity in cultured cells has been observed previously. 16 Indomethacin inhibits not only COX activity but also prostaglandin transport.…”
Section: Discussionmentioning
confidence: 55%
“…8 A distinct role for phospholipase A2 (PLA 2 ) and prostaglandin E2(PGE 2 ) EP2 receptors in swelling-induced activation of regulatory processes in single cells has been demonstrated. 9 Prostaglandin E 2 and PGI 2 enhance outward current and renin secretion from JG cells. 10 In the study presented here, we hypothesized that JG cells respond to a decrease in extracellular osmolality by water uptake, Cyclooxygenase (COX)-dependent prostaglandin formation and renin release.…”
mentioning
confidence: 99%
“…As shown in Figure 3 NDGA added to the extracellular fluid is able to block the swelling-activated chloride current within seconds. It is, therefore, very unlikely that inhibition of lipoxygenase by NDGA (Lambert et al, 1987) or gossypol (Hamasaki & Tai, 1985) is responsible for the observed effect, since the time needed to induce leukotriene production after reduction of extracellular osmolarity in Ehrlich cells is 5 to 10 min (Lambert et al, 1987). Furthermore, NDGA as well as gossypol impede the cyclic AMP-dependent chloride currents (at albeit higher concentrations, see below) which is independent of the leukotriene metabolism.…”
Section: Discussionmentioning
confidence: 98%